Identification of sugarcane mosaic and maize dwarf mosaic potyviruses infecting poaceous crops in India - and A. VARMA2, G.P. RAO1, R.K. JAIN2 (Indian Phytopathology, 2002)
Sixteen potyvirus isolates from sugarcane, maize, sorghum and jowar plants showing typical mosaic symptoms under natural field conditions in different locations of India were compared for biological and serological properties. Results based on different hosts reaction and serological assays (DAC-ELISA, ISEM and Western blotting tests) indicated that potyvirus isolates belonged to two distinct species, viz., sugarcane mosaic virus (SCMV) and maize dwarf mosaic virus (MDMV). SCMV was recorded on sugarcane, maize, sorghum and jowar, and MDMV was only on maize and sorghum.